Who Controls Tradition? Religious Authority, Moral Order, And Belonging in Indonesia: The Case of Sambang Punden - Ulil Amri; Rachmad Kristiono Dwi Susilo (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
As a multicultural archipelago, Indonesia sustains local traditions that shape collective identity and social order, including the Sambang Punden ritual in Bulukerto Village, East Java, Indonesia. This study examines how Sambang Punden produces religious authority, regulates moral norms, and defines community boundaries through inclusion and exclusion. The research adopts a qualitative design to capture meanings, interactions, and local social dynamics surrounding the ritual. Data were collected through observation of the ritual sequence, in depth interviews, and document review related to the organization and public framing of the practice. Data analysis followed an interactive process of organizing materials, coding key themes, refining interpretations, and triangulating sources, while using the concepts of power and knowledge, discourse, and governmentality as analytical tools. The findings show that the ritual’s authority and legitimacy are produced and sustained through the roles of elders, customary actors, and village authorities, while also being questioned by differing religious interpretations. The study further indicates that participation supports moral regulation through social expectations and informal monitoring, and it marks community membership by distinguishing insiders from those positioned at the margins. The implication of this research is that local rituals should be analysed as sociological mechanisms that generate authority, sustain moral governance, and produce social boundaries in village life. Sebagai negara kepulauan multikultural, Indonesia memiliki tradisi lokal yang ikut membentuk identitas dan keteraturan sosial, termasuk ritual Sambang Punden di Desa Bulukerto, Jawa Timur, Indonesia. Penelitian ini bertujuan menjelaskan bagaimana Sambang Punden menghasilkan otoritas keagamaan, mengatur norma moral, dan membentuk batas komunitas melalui inklusi dan eksklusi. Penelitian ini menggunakan desain kualitatif untuk memahami makna, interaksi, dan dinamika sosial di sekitar praktik ritual. Data dikumpulkan melalui observasi rangkaian ritual, wawancara mendalam, dan telaah dokumen yang relevan dengan penyelenggaraan serta pembingkaian ritual. Data dianalisis secara interaktif melalui pengorganisasian data, pengodean tema, penajaman interpretasi, dan triangulasi sumber, dengan konsep relasi kuasa pengetahuan, wacana, dan governmentality sebagai alat bantu analitis. Hasil penelitian menunjukkan bahwa otoritas dan legitimasi ritual diproduksi dan dipertahankan melalui peran sesepuh, lembaga adat, dan aktor pemerintahan desa, sekaligus diperdebatkan oleh pandangan keagamaan yang berbeda. Temuan juga memperlihatkan bahwa partisipasi ritual mendorong regulasi moral melalui ekspektasi sosial dan pemantauan informal, serta menandai keanggotaan komunitas melalui batas “di dalam” dan “di luar.” Implikasi penelitian ini menegaskan bahwa ritual lokal dapat dipahami sebagai mekanisme sosiologis yang membentuk otoritas, tata moral, dan batas sosial dalam kehidupan desa.